Influencia de los factores socioculturales en la desnutrición infantil. - Cajamarca Pilco, Fanny Yolanda (2024)
This bibliographic review aims to determine the sociocultural factors in child malnutrition because this is a global problem characterized by high malnutrition rates in children under five. Malnutrition, which affects the growth and development of infants, is caused by factors such as poverty, lack of maternal education, taboos, and cultural beliefs. For this study, the researcher analyzed forty-three publications from various bibliographic sources, including Google Scholar, Bireme, Scielo, Medline, Elsevier, Medigraphic, Redalyc, and PubMed. The selection of documents was carried out under inclusion criteria that contemplate texts published in the last five years for scientific articles and up to 10 years for books, ensuring their relevance in the Health Sciences and Nursing fields. The analysis was carried out using documentary and descriptive methods to identify the determinants associated with child malnutrition. The results highlight that poverty is the factor with the most significant impact, directly affecting low-income families. In addition, customs, beliefs, and cultural taboos related to food were identified, as well as myths about adequate nutrient consumption. It was evident that rural communities, due to geographical distance and living conditions, have higher rates of child malnutrition. In conclusion, child malnutrition is influenced by multiple sociocultural factors, with poverty and cultural beliefs being the most prominent. These findings underscore the need for interventions addressing economic needs and nutrition education in affected communities.